2010
DOI: 10.1016/j.ijpara.2009.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the complement anaphylatoxin C5a by secreted products of parasitic nematodes

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Brugia malayi and Trichinella spiralis, parasitic nematodes, release a metallocarboxypeptidase that inactivates C5a (Rees-Roberts et al, 2010), presumably to prevent eosinophil chemotaxis and activation. Streptococcus pyogenes produces a C5a peptidase (Wexler et al, 1985) that cleaves between His67 and Lys68 (Cleary et al, 1992).…”
Section: Deactivation Of Complement Peptidesmentioning
confidence: 99%
“…Brugia malayi and Trichinella spiralis, parasitic nematodes, release a metallocarboxypeptidase that inactivates C5a (Rees-Roberts et al, 2010), presumably to prevent eosinophil chemotaxis and activation. Streptococcus pyogenes produces a C5a peptidase (Wexler et al, 1985) that cleaves between His67 and Lys68 (Cleary et al, 1992).…”
Section: Deactivation Of Complement Peptidesmentioning
confidence: 99%
“…However, Mf presence did down-regulate mRNA expression of the inflammatory complement component, C5, in HUVEC and HLMVEC. In light of the recent report, that B. malayi Mf secrete a C5a-cleaving serine protease, this suggests that C5 products may be potentially damaging to filarial nematodes [27]. Similarly, mRNA expression of CCL23, a chemoattractant for monocytes, neutrophils and T cells, was downregulated in HLMVEC.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, the proportion of macrophages within these leukocyte populations was significantly lower in Mf implanted rather than adult implanted mice [26]. Previous work has also shown that a serine protease derived from B. malayi Mf abolishes C5a-mediated chemotaxis of granulocytes [27]. Furthermore both adult B. malayi and Mf extracts inhibit hyper-permeability induced by TNF-α or IL-1α, of lymphatic EC monolayers to dextran.…”
Section: Discussionmentioning
confidence: 86%
“…through their surface receptors binding to these byproducts. For instance, the small fragment byproducts such as C5a, an anaphylatoxins, also play an important role in inflammation and especially in host defense against parasites (Rees-Roberts et al, 2010) (Mosser and Brittingham, 1997). These anaphylatoxins can cause mast cell and basophil degranulation, with the release of histamine and other substances that increase vascular permeability and stimulate smooth muscle constriction.…”
Section: Complement Activation and Complement Regulationmentioning
confidence: 99%